A vapor-phase-assisted growth route for large-scale uniform deposition of MoS2 monolayer films. Issue 1 (21st December 2018) - Pareek, Devendra; Gonzalez, Marco A.; Zohrabian, Jannik; Sayed, Mohamed H.; Steenhoff, Volker; Lattyak, Colleen; Vehse, Martin; Agert, Carsten; Parisi, Jürgen; Schäfer, Sascha; Gütay, Levent
Abstract : Optimization of the sulfurization process of thin MoO3 precursor layers, pushing the reaction towards vapor-phase-assisted routes to obtain large-scale, homogeneous monolayer MoS2 . Abstract : In this work a vapor-phase-assisted approach for the synthesis of monolayer MoS2 is demonstrated, based on the sulfurization of thin MoO3− x precursor films in an H2 S atmosphere. We discuss the co-existence of various possible growth mechanisms, involving solid–gas and vapor–gas reactions. Different sequences were applied in order to control the growth mechanism and to obtain monolayer films. These variations include the sample temperature and a time delay for the injection of H2 S into the reaction chamber. The optimized combination allows for tuning the process route towards the potentially more favorable vapor–gas reactions, leading to an improved material distribution on the substrate surface. Raman and photoluminescence (PL) spectroscopy confirm the formation of ultrathin MoS2 films on SiO2 /Si substrates with a narrow thickness distribution in the monolayer range on length scales of a few millimeters. Best results are achieved in a temperature range of 950–1000 °C showing improved uniformity in terms of Raman and PL line shapes. The obtained films exhibit a PL yield similar to mechanically exfoliated monolayer flakes, demonstrating the high optical quality of the prepared layers.